Die effek van sowjet en Oos-Europese veranderings op kommunistiese en sosialistiese denke in Suid-Afrika - Rossouw, G. J. (Koers, 1991)
Vie purpose of (his article is lo determine from a philosophical point of view the extent to which socialist and communist organizations in South Africa have been influenced by the changes that have occurred in Eastern Europe. In order to make such an assessment, it is necessary to identify the nature of the events that occurred in Eastern Europe and the Soviet Union. This aspect is discussed in the first section of this article. Following this it is argued that different socialist and or communist groups have been influenced in different ways by the Easi-bloc events. In order to demonstrate this difference, the way in which three different political groups in South Africa have been influenced will be highlighted. These groups are the AN C (and its partners the UDF and COSATO), the SACP and the Black Consciousness Movements (like AZAPO). In the concluding section a few observations on the implications of the Eastern European changes for the political and economic debate in South Africa are outlined.